2013
DOI: 10.3390/molecules18033410
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Phenolic Composition and Antioxidant Properties between Vitis coignetiae and Vitis vinifera Seeds Extracts

Abstract: Phenolic compounds were extracted from European and Japanese grapevine species (Vitis vinifera and V. coignetiae) seeds using 80% methanol or 80% acetone. The total content of phenolic compounds was determined utilizing Folin-Ciocalteu's phenol reagent, while the content of tannins was assayed by the vanillin and BSA precipitation methods. Additionally, the DPPH free radical and ABTS cation radical scavenging activities and the reduction power of the extracts were measured. The HPLC method was applied to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…The obtained values can be divided into 3 clusters: the first one including samples with tannin values between 0 mg g −1 and 10 mg g −1 (light grey bars); the second group with concentrations between 10 mg g −1 and 30 mg g −1 (dark grey bars); varieties with seeds presenting amounts of tannins greater than 30 mg g −1 (black bars). All these results were consistent with the data reported by Weidner et al 42 In general, the significant level variations of the phenolic concentrations observed in seeds and skins of different accessions could be strongly associated with various endogenous and exogenous factors, such as climate, berry size, grapevine genetics and nutrients. 40 In Tables 2-4 are reported the biochemical profiles of all the samples, as the amount of each secondary metabolite detected and investigated by LC-MS analysis.…”
Section: Food and Function Papersupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained values can be divided into 3 clusters: the first one including samples with tannin values between 0 mg g −1 and 10 mg g −1 (light grey bars); the second group with concentrations between 10 mg g −1 and 30 mg g −1 (dark grey bars); varieties with seeds presenting amounts of tannins greater than 30 mg g −1 (black bars). All these results were consistent with the data reported by Weidner et al 42 In general, the significant level variations of the phenolic concentrations observed in seeds and skins of different accessions could be strongly associated with various endogenous and exogenous factors, such as climate, berry size, grapevine genetics and nutrients. 40 In Tables 2-4 are reported the biochemical profiles of all the samples, as the amount of each secondary metabolite detected and investigated by LC-MS analysis.…”
Section: Food and Function Papersupporting
confidence: 93%
“…42 A protein precipitation assay was used to determine the presence of both condensed and hydrolyzed tannins in seed sample extracts. The results, expressed as mg CE per g of SFW, are reported in Fig.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The phytochemical analysis of red grape skin reveals the presence of phenolic compounds such as proanthocyanidins, ellagic acid, myricetin, quercetin, rutin, kaempferol, trans-resveratrol, cyanidin-3-glucoside, delphinidin-3-O-glucoside (myrtillin), petunidin-3-O-glucoside, peonidin-3-O-glucoside, malvidin-3-O-glucoside [39,40]. Furthermore, grape seeds are a rich source of polyphenols, which are characterized by a variety of properties, such as antibacterial and antioxidant activities [41,42]. Significant variations in the levels of total phenolic compounds, flavonoids, and anthocyanins in skins and seeds from different varieties of red grapes have previously been reported [41-43].…”
Section: Discussionmentioning
confidence: 99%
“…seeds, rose myrtle ( Rhodomyrtus tomentosa ), Mysore raspberry ( Rubus niveus ), white sorghum, or carrot (82, 8688, 90, 118, 160162). …”
Section: The Venus Flytrap (Dionaea Muscipula Solander Ex Ellis)mentioning
confidence: 99%